Implementasi Lean Manufacturing dan Kaizen untuk Meningkatkan Produktivitas di Lantai Produksi - Linda Theresia; Gadih Ranti; Ray Kreshna (Institut Teknologi Indonesia, 2020)
Currently the industry is trying to improve its competitiveness. This makes the manufacturingindustry needs to adapt the Lean-Kaizen concept. Lean-Kaizen means eliminating waste through small improvements made on an ongoing basis. This research takes a case study at PT Inoac Poltechno Indonesia, which is engaged in foam production. The current production target is only 56% of the planned target. Besides that, there are found many defective products and activities that have no added value. Furthermore, a map of the current condition is made to find waste and know the kaizen that will be carried out. Furthermore, a future map was developed with work standardization and Value Stream Mapping to determine activities that have no added value. Calculation of Waste Assessment Model (WAM), shows the biggest waste is defect (26.73%), inventory (15.79%), and waiting (13.35%). This study found that by adding trolley, adding operators, making SOPs, scheduling engine maintenance would make non-value added (NVA) activities decrease from 29.95% to 20.5%. Process Cycle Efficiency increased from 22.31% to 28.25% (thus fulfilling international PCE requirements for the manufacturing industry). Keyword : Lean-Kaizen, productivity, waste